Digital Marketing and Sustainable Tourism for Tourist Villages in Bangli Regency - I Putu Aban Wibawa; I Putu Astawa; Ni Made Rai Sukmawati; I Wayan Basi Arjana; I Gusti Putu Sutarma (International Journal of Glocal Tourism, 2022)
Purpose: This research is to analyze the application of digital marketing to support sustainable tourism in each tourist village in Bangli Regency, Bali, Indonesia. Research methods: The data collection method used in this study is a phenomenological approach. From the phenomena that happens, the researchers understood it more deeply by looking for concepts and theoretical foundations that are relevant. Findings: The digital marketing model can make it easier for tourists to find tourist villages in Bangli Regency. It is also hoped that the negative impact on the natural environment caused by conventional promotional media can be reduced. Implication: The outcome of this research is a digital marketing model that supports sustainable tourism in each tourist village in Bangli Regency from an environmental, economic, and socio-cultural perspectives.